Carl Einstein: vanguardia y crítica de la vanguardia - Amargós, Joan Ibáñez (Revista de Filología Alemana, 2008)
This article deals with the different stages and key concepts in the works of Carl Einstein, cubist theoretician, ethnologist and early-expressionist prose writer. His complete works are examined along four decades, from the experimentalist stage of the avant-garde to his turn to cultural criticism, positions related to critical theory and committed literature. This paper is focussed on central texts for the different stages, which are also representative with regard to the complete works. The analysis of Einstein’s literary works, as well as the exploration of his criticism on the written medium, are a significant part of the article, supported by his researches about cubism and African art, and by his aesthetic theory.